Effect of Seed Colouring on Seed Quality and Bruchid Damage in Soybean - K. KESHAVULU; V. KRISHNASAMY (Seed Research, 2026)
Seed coloured with botanical dyes, namely flower extract of Hibiscus rosasinensis, root extract of beet root and rhizome extract of turmeric, synthetic chemical dyes and polykotes at 100 ml/kg, 1% and 3 g/kg of seed, respectively were evaluated for seed quality and bruchid (Callosobruchus chinensis) damage in soybean seeds. The study indicated that coloured seeds showed differences in seed quality and insect damage. Seeds coated with H. rosasinensis and polykote colours showed higher per cent germination, root and shoot length and seedling vigour index compared to control. Synthetic chemical dye and red polykote protected the seeds from bruchid up to one month storage.